Intranasal Antibody Gene Transfer in Mice and Ferrets Elicits Broad Protection Against Pandemic Influenza - Limberis, Maria P. (Sci Transl Med, 2013)
The emergence of a new influenza pandemic remains a threat that could result in a substantial loss of life and economic disruption worldwide. Advances in human antibody isolation have led to the discovery of monoclonal antibodies (mAbs) that have broad neutralizing activity against various influenza strains, although their direct use for prophylaxis is impractical. To overcome this limitation, our approach is to deliver antibody via adeno-associated virus (AAV) vectors to the site of initial infection, which, for respiratory viruses such as influenza, is the nasopharyngeal mucosa. AAV vectors based on serotype 9 were engineered to express a modified version of the previously isolated broadly neutralizing mAb to influenza A, FI6. We demonstrate that intranasal delivery of AAV9.FI6 into mice afforded complete protection and log reductions in viral load to 100 LD(50) (median lethal dose) of three clinical isolates of H5N1 and two clinical isolates of H1N1, all of which have been associated with historic human pandemics (including H1N1 1918). Similarly, complete protection was achieved in ferrets challenged with lethal doses of H5N1 and H1N1. This approach serves as a platform for the prevention of natural or deliberate respiratory diseases for which a protective antibody is available.